0069 Dementia Simulation Programme. (1st November 2014) - McDonald, Rozz; Merriman, Clair; Benn, Toby
Abstract : Background/context: The population of people who develop Dementia is growing as is the commitment to providing timely and appropriate responses as evidenced by the Government led 'Dementia Challenge'. Much attention has been drawn to the skills and capabilities of the Health and Social Care workforce and care environments, which are rarely geared to be 'dementia friendly'. This presentation will describe a simulated dementia training day geared towards nurses and allied health professionals which incorporated experiential learning and simulation with a patient actress towards exploring the issues for hospital based staff. Methods and outcomes are discussed alongside barriers and facilitators for others considering these methods. Methodology (used or planned): Participants were asked to contribute towards this pilot training package by simulating their typical responses in a range of scenarios that are common for people with dementia. These included issues around communication difficulties, behaviour which challenges, and receptive language difficulties. Participants were also asked to perform a range of simple activities using an ageing suit which enabled them to further understand and empathise with the complex difficulties of older adults with dementia. Throughout the scenarios, small 'teaching' segments were embedded through discussion of the issues following a particular format The environment was discussed, and a range of environmental and assistive technology solutions were demonstrated. Participants then developed an action plan for their own work area based on the day, and a second follow-up day was planned to review and progress these into action. Results/outcomes (anticipated or recorded to date): Teams will be better prepared to look after patients in hospital based settings. In patient environments will be more 'dementia friendly'. Potential impact: Dementia patients experiences of being cared for in hospital will be improved and untoward incidents/complaints will be reduced. References: DH (2009). Living Well with Dementia: A National Dementia Strategy. Available at https://www.gov.uk/government/publications/living-well-with-dementia-a-national-dementia-strategy [accessed June 2014] DH (2012). Prime Minister's Challenge on Dementia. Available at https://www.gov.uk/government/publications/prime-ministers-challenge-on-dementia [accessed June 2014]